Parahydrogen-induced polarization in the hydrogenation of lignin-derived phenols using Wilkinson's catalyst - Kim, Kwang Ho; Choi, Joon Weon; Kim, Chang Soo; Jeong, Keunhong (Elsevier BV, 2019)
We herein report our new hydrogenation strategy realized at room temperature and atmospheric pressure for stabilizing lignin model phenols in the presence of Wilkinson's catalyst (RhCl(PPh3)(3)). To the best of our knowledge, we first employed a parahydrogen for the hydrogenation study of lignin-derived reactive phenols with vinyl- and allyl groups, and parahydrogen-induced polarization was observed in-situ using a benchtop NMR spectroscopic system. The results clearly showed the saturation of those reactive functional groups with Wilkinson's catalyst as well as enhanced spin polarizations, which will be a firm basis for developing new types of hydrogenation catalysts in mild conditions. The benchtop NMR system integrated with the use of parahydrogen and homogeneous hydrogenation processes employed in this study could provide insights toward new fundamental applications. Furthermore, this strategy shows potential for developing a new practical analytical tool with highly polarized nuclear spins in the lignin-based biorefineries.